William G. Rosenberg, Marilyn B. Young, Transforming Russia and China. Revolutionary Struggle in the Twentieth Century, New York—Oxford, Oxford University Press 1982, ss. 397 - Adam Czarnota (Czasopismo Prawno-Historyczne)
Recenzja: William G. Rosenberg, Marilyn B. Young, Transforming Russia and China. Revolutionary Struggle in the Twentieth Century, New York—Oxford, Oxford University Press 1982, ss. 397.